2023
DOI: 10.2147/ijn.s420967
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Stem Cell-Derived Exosomes Regulate Anti-Inflammatory and Osteogenesis in Periodontal Ligament Stem Cells and Promote the Repair of Experimental Periodontitis in Rats

Xin Qiao,
Jie Tang,
Lei Dou
et al.

Abstract: Purpose Dental pulp stem cell-derived exosomes (DPSC-EXO), which have biological characteristics similar to those of metrocytes, have been found to be closely associated with tissue regeneration. Periodontitis is an immune inflammation and tissue destructive disease caused by plaque, resulting in alveolar bone loss and periodontal epithelial destruction. It is not clear whether DPSC-EXO can be used as an effective therapy for periodontal regeneration. The purpose of this study was not only to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(82 reference statements)
1
4
0
Order By: Relevance
“…This agreed with Babaki et al [22] and Zhuang et al [23] who found cell proliferation enhancement in the cells treated with 0.2 mg/mL MTA and 50 µg/mL sEVs respectively. Using two different concentrations of sEVs showed that DPSC-sEVs promoted cell proliferation in a concentration-dependent manner which is in agreement with Qiao et al [39]. In our study, the combination group showed the greatest cell proliferation at the two different intervals in comparison with other groups indicating the addition of sEVs enhanced the MTA biocompatibility and cell proliferation ability.…”
Section: Discussionsupporting
confidence: 92%
“…This agreed with Babaki et al [22] and Zhuang et al [23] who found cell proliferation enhancement in the cells treated with 0.2 mg/mL MTA and 50 µg/mL sEVs respectively. Using two different concentrations of sEVs showed that DPSC-sEVs promoted cell proliferation in a concentration-dependent manner which is in agreement with Qiao et al [39]. In our study, the combination group showed the greatest cell proliferation at the two different intervals in comparison with other groups indicating the addition of sEVs enhanced the MTA biocompatibility and cell proliferation ability.…”
Section: Discussionsupporting
confidence: 92%
“…In cell culture experiments, an experimental setup is prepared by keeping the cells of organisms in in vitro environments, in specifically manufactured containers, by controlling environmental conditions such as temperature and humidity, and by protecting them from contamination. Another advantage of cell culture studies is that cells taken from different kinds of living things, including humans, can be kept alive in a laboratory environment, cells taken from any tissue or organ can be used, and it eliminates many ethical concerns [14][15][16][17][18][19] . Different in vitro studies are carried out to determine whether dental materials have cytotoxic potential.…”
Section: Discussionmentioning
confidence: 99%
“…During the apoptosis process, the chromatin block (nuclear fragments) formed by the condensation and fragmentation of nuclei and the membrane vesicles gradually divide into different sizes of vesicles, including exosomes, microvesicles and ABs. 33 , 34 Stem cell-derived exosomes increase the expression levels of osteogenic genes, regulate the polarization of macrophages and accelerate bone formation in defects of alveolar bone; 35 , 36 MSC-derived microvesicles showed a therapeutic potential for the treatment of clinical cartilage injury. 37 ABs are the major product of apoptotic cells and contain large amounts of regulatory molecules that are involved in a wide range of biological functions.…”
Section: Discussionmentioning
confidence: 99%